Komparasi Geokimia Batuan Gunung Api Kuarter dan Tersier di Tepian Selatan Lampung - Irzon, Ronaldo (BRIN Publishing, 2020)
The presence of volcanic rocks in Sumatra is due to the subduction of the Indian-Australian Ocean Plate under the West Sumatra Plate since the Eocene. Tanggamus Regency situated at the southern edge of Lampung with the occurrence of several Tertiary and Quaternary volcanic rock units. The aim of this study is to compare the geochemical composition of Tertiary volcanic rocks from the Hulusimpang Formation and Quaternary volcanic rocks from Mount Tanggamus in the Tanggamus Regency. XRF and ICP-MS devices were used to determine the compositions of major oxides, trace elements, and rare earth elements in this study. Based on geochemical characters, samples from the Hulusimpang Formation are calc-alkaline volcanic rocks, metaluminous to peraluminous, and in the basaltic trachyandesite to rhyolite ranges. Quaternary samples are in a narrower range of silica content and tend to be metaluminous. This study proves that the two rock groups originate from the same magma but with crustal contamination during differentiation. The two volcanic should experience through different formation processes based on the slope of the heavy-REE and the type of Eu anomaly.